PEG-coumarin nanoaggregates as π–π stacking derived small molecule lipophile containing self-assemblies for anti-tumour drug delivery. Issue 4 (4th March 2018) - Behl, Gautam; Kumar, Parveen; Sikka, Manisha; Fitzhenry, Laurence; Chhikara, Aruna
Abstract: Polymeric self-assemblies formed by non-covalent interactions such as hydrophobic interactions, hydrogen bonding, π–π stacking, host-guest and electrostatic interactions have been utilised widely and exhibit controlled release of encapsulated drug. Beside carrier-carrier interactions, small molecule amphiphiles exhibiting carrier-drug interactions have recently been an area of interest for cancer drug delivery, as most of the hydrophobic anti-tumour drugs are aromatic and exhibit π–π conjugated structure. In the present study PEG-coumarin (PC) conjugates forming self-assembled nanoaggregates were synthesised with PEG (polyethylene glycol) as hydrophilic block and coumarin as small molecule lipophilic segment. Curcumin (CUR) as model conjugated aromatic drug was loaded in to the nanoaggregates via dual hydrophobic and π–π stacking interactions. The interactions between the conjugates and CUR, drug release profile and in vitro anti-tumour efficacy were investigated in detail. CUR-loaded nanoaggregate self-assembly was driven by π–π interactions and a maximum loading level of about 18 wt.% (~60 % encapsulation efficiency) was achieved. The average hydrodynamic diameter (Dav ) was in the range of 120–160 nm and a spherical morphology was observed by transmission electron microscopy (TEM). A sustained release of CUR was observed for 90 h. Cytotoxicity evaluation of CUR-loaded nanoaggregates on pancreatic cancer cell lines indicated higher efficacy, IC50 ~11 and ~15 μM as compared to free CUR, IC50 ~14 and ~20 μM on human pancreatic carcinoma (MIA PaCa-2) and human pancreatic duct epithelioid carcinoma (PANC-1) cell lines respectively. PC conjugates provided a new strategy of fabricating nanoparticles for drug delivery and may form the basis for the development of advanced biomaterials in near future.